CGE Analysis of Regional Policy in Northern Kyushu Area - Hiroshi Sakamoto (European Regional Science Association (ERSA), 2010)
This study develops a policy model under the hierarchical administration system of the regional economy in Japan. In case of Japan, a hierarchy of national, prefectural, and municipal (city) administration exists, and a different regional policy in these each hierarchies can be set up. Generally, the policy and its evaluation might be different whether should give priority to national interests or to each region's interests. To show such a situation, quantitatively analysis by using the computable general equilibrium model (CGE model) is examined. Concretely, Kitakyushu City and Fukuoka City are taken up as an administrative region at the city level. Together with these two cities and surrounding areas, it becomes Fukuoka Prefecture. On the other hand, the case of including Yamaguchi Prefecture, the adjacent prefecture, in these regions exists. In this case, it can be called Northern Kyushu Area by combining Fukuoka Prefecture and Yamaguchi Prefecture, and such a large area also becomes important in the regional policy as higher hierarchy. Five regions including the rest of Japan are focused on this study. Moreover, due to availableness of the input-output tables of these regions, respectively, the data base to develop the CGE model is estimated after tabulating the interregional input-output table.
Keywords: C68; D58; O53; R13; 330; Northern Kyushu; Hierarchy of administration; Regional policy; CGE model